The Effect of Social Media and Price on Purchasing Decisions on Solo Tea Drinks in Jakarta City - Evan Justin; Iyus Wiadi (Journal of Economics and Business (JECOMBI), 2025)
There has been a significant increase in tea production in West Java Province, where data from the Central Bureau of Statistics shows that West Java has become the largest tea producing province, with a production volume of 82,100 tons, equivalent to 66.92% of total tea production in Indonesia. In addition to being the largest tea producer, West Java also has the largest tea plantation, covering an area of 78,500 hectares. Seeing this phenomenon, this study aims to determine the effect of social media and price on purchasing decisions for “Solo Tea” tea drinks in Jakarta City. The method used in this research is a quantitative approach, where questionnaires will be distributed to residents of Jakarta City. Based on this, the data used in this study is primary data, which will be processed using SPSS Version 26 and analyzed using multiple linear regression tests to determine the effect of each variable. The results of this study indicate that social media variables have a significant influence on purchasing decisions, and price variables also have a significant effect on purchasing decisions. Furthermore, when viewed simultaneously, social media and price variables have a significant effect on purchasing decisions for “Solo Tea” tea drinks in Jakarta City.